Implementation of Grant Agreement in the Sukolilo Barat Village Fishermen Empowerment Program by Laznas LMI Bangkalan - Roziqin, M. Zeinur; Choiri, Muttaqin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
In encouraging welfare in the community, there needs to be a superior program carried out by the government or a related agency so that welfare can be achieved. This study was conducted with the aim of determining the form of conformity of the implementation of the grant agreement and empowerment carried out by Laznas LMI Bangkalan in running its program. The follow-up of this study is to provide an overview of the practice of the grant agreement in the community, as well as to encourage a more effective concept of community empowerment. The method used is qualitative, data collected through interviews, literature studies and observations. The results of the study show that in practice, it is in accordance with the practice of the grant agreement in Islamic teachings, because it has met the pillars and requirements. At the same time, the concept of empowerment itself shows the level of success achieved, because the people of West Sukolilo Village have gone through the stages in achieving welfare. Such as the awareness of the community to achieve welfare. Second, there is a driving force and person in charge of making the program a success. Third, the implementation of monitoring and assistance in providing broader knowledge. Fourth, there is support for infrastructure in supporting the implementation of the program. Fifth, the utilization of human resources to maintain solidarity and achieve good cooperation for the common welfare.